2021
DOI: 10.3390/cancers13246271
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of Complications and Unplanned Readmissions after Pancreatoduodenectomy for Pancreatic and Periampullary Tumors: Results from a Single Academic Center

Abstract: Background/Objectives: Complications after pancreatoduodenectomy (PD) lead to unplanned readmissions (UR), with a two- to threefold increase in admission costs. In this study, we aimed to create an understanding of the costs of complications and UR in this patient group. Furthermore, we aimed to generate a detailed cost overview that can be used to build a theoretical model to calculate the cost efficacy for prehabilitation. Methods: A retrospective cohort analysis was performed using the Dutch Pancreatic Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The rate of POC following PD remains high despite advanced surgical skills and perioperative management [ 1 ]. In addition, the mortality rate of PD ranges from 1.7% to 4.2% [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of POC following PD remains high despite advanced surgical skills and perioperative management [ 1 ]. In addition, the mortality rate of PD ranges from 1.7% to 4.2% [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rijssen et al [ 3 ] showed that POPF was mainly attributable to worse mortality. Moreover, Linnemann et al [ 1 ] showed that medical costs increased by about 50% after POCs following PD. Thus, adequate prevention or treatment of POPF can contribute to reducing the mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redirecting this funding towards prehabilitation interventions at the outset could substantially enhance surgical outcomes. Notably, a correlation exists between total hospital admission costs and the comprehensive complication index 5 . This emphasizes that not only the most severe but every additional complication has impact.…”
Section: Introductionmentioning
confidence: 99%
“…Another important argument to estimate the post-operative risk is to reduce the adverse consequences of the complications. It is known that complications can lead to multiple organ failure or mortality, prolong hospital stay and/or required readmission and increased costs [ 24 , 25 , 26 ]. A complicated course after pancreatoduodenectomy may lead to impaired long-term survival [ 27 ].…”
Section: Introductionmentioning
confidence: 99%